Seams like murder : a sewing studio mystery - Howell, Dorothy (Dorothy A.) (Howell, Dorothy. Sewing studio mystery, 2022)
Abbey has barely arrived in the quaint, quiet town of Hideaway Grove before things turn from blissful to bloody--as the new librarian is mowed down by a car. The only witness on the scene isn't much help, aside from handing Abbey the bag of books dropped by the victim. Even worse, the sheriff's office seizes Abbey's car because of a suspicious dent in the right front fender. While she waits for the problem to be sorted out, Abbey is drawn into a charity sewing project--even though she can't tell a bobbin from a seam ripper. Before she knows it, she's graduating from pillowcase dresses to aprons, setting up a studio in a back room of her aunt's bakery, and making plans to participate in the upcoming craft fair. But through it all, she keeps looking for patterns and possible conflicts in the late librarian's personal, professional, and romantic life. Then a shocking discovery sends her in a new direction, and as the truth begins to unspool, she's got a notion about who's guilty...--